Access to Education under U.S. Law and Some Recommendations for Vietnam - TRINH, Duy Thuyen; NGUYEN, Truong Thanh Hai; MAI, Pham Bao Tran (Journal of Research in Educational Sciences; Vol 15 No 1 (2024): JRES, Volume XV, Issue 1(17), Summer 2024DO - 10.14505/jres.v15.1(17).03, 2024)
Purpose: The right to education is a fundamental right for all members of society, serving as a cornerstone for promoting population growth and facilitating equal educational opportunities without discrimination. Vietnam, a nation committed to fulfilling its international obligations, including ensuring access to education as a fundamental constitutional right, is not without its challenges. These challenges, ranging from inadequate infrastructure to social and economic disparities, present opportunities for growth and improvement. This article examines the legal framework and implementation of education access laws in the United States, with the aim of identifying strategies that can be selectively adopted to enhance Vietnam's education system. By doing so, Vietnam can create a supportive legal environment for innovation in education and training, paving the way for a brighter future. Methodology: The study involves a comparative analysis of the education systems in Vietnam and the United States, focusing on the legal provisions and practical implementations that facilitate access to education. Findings: The analysis reveals that, despite Vietnam's commitment to ensuring education as a fundamental constitutional right, the country faces challenges such as inadequate infrastructure and social and economic disparities. These challenges present opportunities for improvement through the adoption of best practices from the U.S. education system. Originality: This research provides a unique perspective by highlighting the potential for Vietnam to enhance its education system through the selective adoption of strategies from the U.S. legal and educational framework. This approach aims to create a supportive legal environment for innovation in education and training, contributing to a brighter future for Vietnam.